A secure protocol for exchanging cards in P2P trading card games based on transferable e-cash - Silva, Marcos V. M.; Simplicio Jr., Marcos A. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2015: Anais do XV Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2015.20094, 2015)
Trading card games (TCG) distinguish from traditional card games mainly because the cards are not shared between players in a match. Instead, users play with the cards they own (e.g., purchased or traded with other players), which corresponds to a subset of all cards produced by the game provider. Even though most computer-based TCGs rely on a trusted third-party (TTP) for preventing cheating during trades, allowing them to securely do so without such entity remains a challenging task. Actually, potential solutions are related to e-cash protocols, but, unlike the latter, TCGs require users to play with the cards under their possession, not only to be able to pass those cards over. In this work, we present the security requirements of TCGs and how they relate to e-cash. We then propose a concrete, TTP-free protocol for anonymously trading cards, using as basis a secure transferable e-cash protocol.